El mosaico comun del frijol (Bean common mosaic virus) : Metodologia de investigacion y tecnicas de control - Morales, Francisco José (International Center for Tropical Agriculture, 1979)
BCMV causes losses of up to 50 percent and produces mosaic and systemic necrosis on the plant. It is seed borne and several species of aphids are vectors; it is transmitted mechanically with relative facility. A description is given of the methodology used by CIAT to identify and manage the virus and its strains during the evaluation process of bean material resistant to the virus in the breeding programs. (CIAT)